Impact of competency-based teacher education on mathematical conceptual understanding in Kenyan teacher training colleges - Dickens Okach Ngicho; Milcah Njoki Nyaga; Elizabeth Atieno Obura (International Journal of Evaluation and Research in Education (IJERE), 2026)
Pre-service teachers of mathematics must be systematically prepared as effective teachers through structured instruction that targets conceptual understanding and enables them to develop the competencies needed to address real-world problems. This paper reports the findings from a study aimed at assessing the impact of competency-based teacher education (CBTE) on mathematical conceptual understanding among pre-service teachers in Kenyan teacher training colleges (TTCs). The study was guided by scientific management and constructivist theories, emphasizing structured instructional planning and learner-centered facilitation. A mixed-methods research design was employed to collect data from 371 pre-service teachers using questionnaires and interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed thematically. The study revealed a significant positive association between CBTE variables and pre-service teachers’ mathematics conceptual understanding (Spearman’s rho(371)=0.198, p˂0.05). Further, regression analysis indicated that CBTE instructional practices significantly predicted pre-service teachers’ conceptual understanding (F(7,363)=7.791, p˂0.05), accounting for 13.1% of the variance. Qualitative findings corroborated these results, showing that learner-centered and technology-supported instruction enhances conceptual understanding. The findings suggest that holistic and coherent CBTE implementation can enhance trainees’ understanding of mathematics concepts.